2023
DOI: 10.1002/ccr3.7521
|View full text |Cite
|
Sign up to set email alerts
|

Syringomatous adenoma of the nipple: A case series and systematic review

Abstract: Syringomatous adenoma of the nipple (SAN) is known to be a rare benign breast neoplasm. With a few cases documented in the literature, preoperatively diagnosing this tumor is a challenge, which often leads to invasive procedure such as mass excision with nipple removal. This study was aimed at presenting a case report of SAN and to conduct a review of published cases. Literature search was conducted through PubMed databases. Articles published from year 1983 to March of 2022 were included. Only histologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Although a recognized association exists, the definitive link between NA and subsequent breast cancer development or a direct causal relationship for NA transforming into breast cancer has not been established but cannot be ruled out. 1,2,6 In our study, 10.34% of cases presented with a malignant or premalignant co-diagnosis, a statistically significant occurrence. All cases of malignant disease during follow-up were identified in the co-diagnosis group.…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…Although a recognized association exists, the definitive link between NA and subsequent breast cancer development or a direct causal relationship for NA transforming into breast cancer has not been established but cannot be ruled out. 1,2,6 In our study, 10.34% of cases presented with a malignant or premalignant co-diagnosis, a statistically significant occurrence. All cases of malignant disease during follow-up were identified in the co-diagnosis group.…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies reported diverse clinical presentations, including skin growth, rash, nipple discharge, erosive lesion, or other symptoms. 2,6 Our findings highlight a nodule or mass as the predominant clinical symptom, occurring more frequently in the co-diagnosis group. Symptoms like erythema, pain, and nipple deformity were more prevalent in the CONA, whereas ulceration and discharge were more common in the ONA group.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations